Os Quiero, Os Respeto, Os Necesito - Olhares Nomadas (Portugal, 2011)
This is the story of a generation who has waited for political change for many decades and finally found it in the 2011 Spanish Revolution. On May 15, 2011, thousands of people swarmed Puerta Del Sol. The “15-M” Movement, as it is now called, is the story of a collective awakening. The “Indignant People” have taken to Spain’s main squares and started a grassroots revolution. By camping in the public squares by the hundreds, they are demanding that their voices be heard.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films